Responses of gas exchange and growth in Merkus pine seedlings to expected climatic changes in Thailand - Koskela, Jarkko (Wiley, 2008)
Responses of gas exchange and growth in Merkus pine (Pinus merkusii Jungh. et de Vriese) seedlings to changing climate were analysed for high- and low-altitude sites in Thailand. A gas exchange model, based on the optimality approach, derived the effect of drought from the probability of rains. A carbon-and nitrogen-balance growth model applied structural regularities of a tree and a modification of functional balance between foliage and fine roots as growth-guiding rules. Adaptation to local climates was incorporated in the models. The simulations yielded physiologically reasonable behaviour for annual photosynthesis (A) and transpiration (E) in relation to the distributions of precipitation over the course of a year. An annual temperature increase of 2 °C and a prolonged dry season (scenario 2) reduced A by 5-11% and E by 5-8% as compared to present climate (scenario 1). Doubled CO2 concentration and the increased temperature (scenario 3) enhanced A by 56-59% and E by 14%. Simultaneously these changes (scenario 4) increased A by 41-53% and E by 1-5%. Simulated growth in scenario 1 fitted reasonably well to field data. By the age of five years, simulated total biomass (TB) and height (h) were reduced by 31-67% and 12-42%, respectively, in scenario 2 compared to scenario 1. In scenario 3, TB and h increased by 279-330% and 94-191%, and in scenario 4, by 83-241% and 55-69%, respectively. Large increases in TB and h are explained by the exponential growth phase of the young seedlings. These results suggest that climatic changes enhance growth and thus shorten the duration of the grass stage in these seedlings. However, the effects of climatic changes on growth depend strongly on how rainfall seasonality is altered in SE Asia because prolonged drought episodes may retard the fertilizing effects of the increasing CO2 concentration.